Water-soluble phenanthroline complexes of rhodium, iridium and ruthenium for the regeneration of NADH in the enzymatic reduction of ketones - Canivet, Jerome; Süss-Fink, Georg; Stepnicka, Petr (My University, 2007)
The nicotinamide coenzyme NADH, consumed in enantioselective reduction of ketones catalysed by alcohol dehydrogenases, needs to be regenerated in order to maintain enzymatic activity. We therefore studied the catalytic potential of the cationic complexes [(eta(5)-(CMe5)-Me-5)Rh(NnN)Cl](+) (1: N boolean AND N = 1,10-phenanthrohne; 2: NnN = 5 -nitro-1, 10-phenanthroline; 3: NnN = 5-amino-1, 1 0-phenanthroline), [(eta(5)-C5Me5) Ir(N boolean AND N)CI](+) (4: N boolean AND N = 5-nitro-1, 10-phenanthroline) and [(eta(6)-C-6,Me-6)Ru(N boolean AND N)Cl](+) (5: NnN = 5-nitro-1,10-phenanthroline), isolated as the water-soluble chloride salts, for transfer hydrogenation of NAD(+) to give NADH in aqueous solution. The best results were obtained with rhodium complex 1, which gave catalytic turnover frequencies up to 2000 h(-1) in aqueous solution at pH 7 and 60 degrees C with sodium formate as the hydrogen source. When this NADH-regenerating catalytic system is combined with NADH-dependent enzymes, it is possible to chemoenzymatically reduce prochiral ketones such as acetophenone or 4-phenylbutan-2-one with high enantioselectivity. Combination of horse liver alcohol dehydrogenase (HLADH) or alcohol dehydrogenase from Rhodococcus sp. (S-ADH) with 1/formate as the NADH-regenerating system resulted in ee values up to 98 %, depending on the nature of the substrate and the enzyme. In order to explain the different catalytic activities, the electrochemical behaviour of complexes 1-5 has been studied. ((c) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007)
Keywords: cationic complexes; cofactor regeneration; chemoenzymatic catalysis; enantioselective catalysis; transfer hydrogenation; ASYMMETRIC TRANSFER HYDROGENATION; BIOORGANOMETALLIC CHEMISTRY; REGIOSELECTIVE REDUCTION; AROMATIC KETONES; ENANTIOSELECTIVE REDUCTION; ELECTROCHEMICAL PROPERTIES; 1; 4-NADH DERIVATIVES; OXIDATION REACTIONS; MECHANISTIC ASPECTS; CRYSTAL-STRUCTURE